Expression and inducibility of P450 enzymes during liver ontogeny - Rich, Kim J.; Boobis, Alan R. (Microscopy research and technique, 1997)
Several approaches, including immunoquantification of individual enzymes, profiling of substrate activities by immunoinhibition using highly specific polyclonal and monoclonal antibodies, and the estimation of corresponding mRNAs with nucleic acid probes, have been used to investigate the ontogeny of cytochromes P450 in livers of rodents and man. CYP1A1 is expressed very early in development in rodents, whereas most other enzymes either appear at or near birth (CYP2B, CYP2C23, and CYP3A) or between 2 and 4 weeks following birth (CYP2A, CYP2C6, CYP2C7, CYP2C11, CYP2C12, and CYP4A10). The constitutive expression of enzymes is subject to regulation by various transcriptional nuclear and/or hormonal factors (CYP2B and CYP2C) or in a sex‐dependent manner (CYP2A, CYP2C11, CYP2C12, CYP3A, and CYP4A10). The enhanced sensitivity and specificity of immunocytochemical and in situ hybridisation studies have revealed differences, with age and xenobiotic treatment, in the intercellular expression of certain P450 enzymes of the liver. For example, in rats, the expression of CYP1A1 and 1A2 is differentially regulated at the level of the individual cell from as early as 24 hours before birth. The human foetal liver relative to rodents has a substantial level of CYP3A and also has the capacity to metabolise a greater repertoire of substrates. Evidence to date suggests that P450 enzymes in man are regulated in a manner similar to that in other animals. The balance between different individual enzymes of cytochrome P450 in foetuses and/or neonates is subject to modulation by xenobiotics, the consequences of which may lead to toxicologically compromised livers with respect to metabolic handling of certain substrates. Microsc. Res. Tech. 39:424–435, 1997. © 1997 Wiley‐Liss, Inc.